Comparative Study on Preventing Security Attacks in Automated Gate System - Erman Hamid; Hani Maisarah Zainal Subari; Norharyati Harum; Robiah Yusof (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This study is conducted to identify the current approach to preventing security attacks in one of the Internet of Things – the Automated Gate System. The question of vulnerability of the Automated Gate System is a critical issue as this system acts as a front line that protects an organization from any security intrusion. A sound security system leads to the cyber and physical security of the organization, enabling the organization to move forward in achieving management goals. The focus is specifically on methods and techniques for security elements used in previous studies, prompting answers to questions on security mechanisms to Automated Gate Systems that are practical and reliable. The literature review shows various studies conducted on this issue, focusing on how an IoT system for automated gates operates, how it works logically and physically, the security level, and the extent to which a gate system is immune from hacking. This study employed the Content Analysis technique, meaning the previous research data were analyzed and summarized scientifically. It continued with interviews conducted with experts and owners of the Automated Gate System. It is a series of activities analyzing and summarizing the scientific 'data' produced by previous research and interviews. The 'data' refers to spoken, written, or visual pictures, words, symbols, meanings, ideas, diagrams, or any message that can be analyzed. The study then focused on a final comparison involving three security techniques on the IoT Gate System: a QR Code System, RFID System, and Vehicle License Plate Recognition System, which is a reliable but practical technique for an IoT Automated Gate System. This study ultimately offers future work to analyze the three selected Automated Gate Systems with a selected security testing technique, with the objective of security but with practical financial capabilities.